Mendulang Suara Generasi Milenial Muslim: Citra Ketua Umum PPP M. Romahurmuziy di Media Sosial - Zulhazmi, Abraham Zakky (IAIN Surakarta, 2018)
This study aims to reveal the image displayed by the General Chairperson of the PPP (Partai Persatuan Pembangunan – The United Development Party). Through social media, M. Romahurmuziy communicates his ideas and portrays himself. In a number of uploads, M. Romahurmuziy appeared with a green turban looped around his neck, a rolled up long-sleeved white shirt, jeans, and a watch. Using the semiotic approach, this research wants to reveal the meaning of M. Romahurmuziy’s fashion style. This research is qualitative and uses Roland Barthes semiotic analysis to reveal the image that M. Romahurmuziy wants to display. The conclusion of this study is that M. Romahurmuziy displays an Islamic, young, and contemporary image. The image is intended to target the Muslim millennial generation.